The Effect of Satisfaction, Customer Loyalty and its Dimension (Cognitive Loyalty, Affective Loyalty and Behavioural Loyalty), Waiting Time, Self-Service Technology Experience, Customer Involvement Level and Trust on Repurchase Intention in Online Food Delivery Service - Gunadi, Renji (2020)
The industry of online food delivery service in the UK faces a deteriorated profitability due to the several factors such as tight competition, a rise of labour cost, strong restaurant’s bargaining power and carrying dual business models. One of the solutions to rise the profitability is by increasing the volume order from customer. Hence, this research aims to investigate the relationship between satisfaction, customer loyalty, and repurchase intention with its antecedents. The previous finding from Bulut (2015), Atchariyachanvanich, Okada and Sonehara (2006), Oliver (2015), Han, Kim and Kim (2011), Blut, Evanschitzky, Vogel and Ahlert (2007), Bloemer and Ruyter (1999), Ladhari and Lecrlerc (2013), Ndubisi (2006), Bhattacherjee (2001), Hellier, Geursen, Carr and Rickard (2003), Chauke and Dhurup (2017), Bielen and Demoulin (2007), and Meuter, Ostrom, Roundtree and Bitner (2000) provide the basis to construct the research framework.